Lower levels of FOXP3 are associated with prolonged inflammatory responses in kidney transplant recipients - Saleh, Qais W.; Mohammadnejad, Afsaneh; Tepel, Martin (Frontiers in Immunology, 2023)
Background Immunosuppressive treatment of kidney transplant recipients is mainly aimed at pro-inflammatory T effector cells, yet they also target the immunosuppressive T regulatory cells. Here, we test the hypothesis that low levels of the master gene regulator of T regulatory cells, forkhead box P3 (FOXP3) splice variants, are associated with prolonged inflammatory responses to stimuli. Methods From blood samples obtained the first – and 29th day post-transplant, we extracted peripheral blood mononuclear cells and measured mRNA levels of Total FOXP3, pre-mature RNA FOXP3 (pre-mRNA FOXP3), full length FOXP3 (FOXP3fl) and, FOXP3 splice variant excluding exon two (FOXP3d2). We defined the primary outcome as the number of days in which C reactive protein (CRP) was above 50 mg/L. CRP levels were gathered in two periods, the first from the second to 29 days post-transplant, and the second from 30 to 57 days post-transplant. The association was tested using adjusted negative binomial regression. Results From 507 included kidney transplant recipients, 382 recipients had at least one CRP measurement >50 mg/L in the first period, median duration of elevated CRP was 4 days [interquartile range (IQR) 2 to 6]. In the second period, 69 recipients had at least one CRP measurement >50 mg/L, median duration of elevated CRP was 3 days [IQR 2 to 5]. In the first period, we found a significant association between lower levels of Total FOXP3 and prolonged duration of CRP elevation, incidence rate ratio 0.61 (95% confidence interval 0.46-0.80), p<0.01. Conclusion Lower levels of total FOXP3 mRNA levels in peripheral blood of kidney transplant recipients are associated with prolonged duration of inflammatory responses regardless of the underlying stimuli.